EVALUATIONS AND THERAPIES OF PATHOLOGICAL PROBLEMS IN WALL, FLOOR, CEILING AND FACADE COATINGS: - Batista, Pedro Igor Bezerra; Macedo, José Vitor da Silva; Pereira, Amanda Peixoto; Póvoas, Yêda Vieira; Lordsleem Jr., Alberto Casado (Encontro Latino-americano e Europeu sobre Edificações e Comunidades Sustentáveis (euroELECS), 2023)
This work aims to investigate the pathological manifestations incident to a public hospital, in order to describe the diagnosis and possible recovery measures. The methodology included the realization of building inspections, collection of information with managers, analysis of architectural projects. The inspections included filling up checklist, photographic report and analysis of the manifestations through damages maps for later formulation of diagnosis, prognosis and suggestion of recovery measures. It is concluded that there are several pathological manifestations in the coatings (ceiling, floor, wall and façade) which occur systematically and at various levels of intensity, evidencing the absence of a management plan and integrated execution of maintenance services of the coating system.